Transboundary perspectives on managing Indonesia's fires - Mayer, J. (2006)
This study explores initiatives in Indonesia, Singapore, and Malaysia to eliminate transboundary “haze” in Southeast Asia and the fires in Indonesia that are its major cause. It outlines reforms and technical programs to improve fire management and reduce smoke pollution and examines the scope for cooperation and conflict among these parties to the Association of South East Asian Nations (ASEAN) Agreement on Transboundary Haze Pollution. The study analyzes how changing administrative structures affect success of fire management and pollution control programs and explains how developing the effective fire management in Indonesia necessary to eliminate transboundary haze will depend on a combination of political will, legal reform, and administrative coordination. Although the ASEAN Haze Agreement lacks enforceable mandatory provisions, it remains a useful vehicle for international pressure and regional cooperation to eliminate transboundary pollution.